The near-optimal feasible space of a renewable power system model - Neumann, Fabian; Brown, Tom (Electric power systems research, 2021)
•A single least-cost solution underplays the degree of freedom in long-term planning.•Systematically explores decision space of generation, storage and grid expansion model.•Study the European power system for CO2 reduction targets between 80% and 100%.•Near the optimum, many similarly costly but technologically diverse solutions exist.•New transmission lines and hydrogen storage appear essential for low-cost solutions. Models for long-term investment planning of the power system typically return a single optimal solution per set of cost assumptions. However, typically there are many near-optimal alternatives that stand out due to other attractive properties like social acceptance. Understanding features that persist across many cost-efficient alternatives enhances policy advice and acknowledges structural model uncertainties. We apply the modeling-to-generate-alternatives (MGA) methodology to systematically explore the near-optimal feasible space of a completely renewable European electricity system model. While accounting for complex spatio-temporal patterns, we allow simultaneous capacity expansion of generation, storage and transmission infrastructure subject to linearized multi-period optimal power flow. Many similarly costly, but technologically diverse solutions exist. Already a cost deviation of 0.5% offers a large range of possible investments. However, either offshore or onshore wind energy along with some hydrogen storage and transmission network reinforcement appear essential to keep costs within 10% of the optimum.